Antagonistic Worlds in “Bananos y hombres,” by Carmen Lyra - Rivera Cerdas, Gineth Tatiana (2021)
This is a detailed study of the topics and political perspective evident in the set of short stories “Bananos y hombres,” by Carmen Lyra. Emphasis is given to the approach to the social and political problems of the period in which the stories were written, and to the critical perspective which is adopted from the voice of the narrator. Thus, light is shed on the political and social commitment which the author assumes as a writer and as an intellectual.